2018
DOI: 10.1093/eurheartj/ehy421
|View full text |Cite
|
Sign up to set email alerts
|

Comparing biomarker profiles of patients with heart failure: atrial fibrillation vs. sinus rhythm and reduced vs. preserved ejection fraction

Abstract: In patients with HFrEF, the presence of AF was associated with a homogeneously elevated cardiovascular risk marker profile. In contrast, in patients with HFpEF, the presence of AF was associated with a more scattered risk marker profile, suggesting differences in underlying pathophysiological mechanisms of AF in these HF phenotypes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
37
0
2

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 52 publications
(43 citation statements)
references
References 30 publications
4
37
0
2
Order By: Relevance
“…Biomarkers of systemic inflammation and collagen turnover are elevated in both AF and HFpEF and are associated with exercise intolerance and abnormalities in diastolic filling . Proteomic analyses suggest a strong link between HFpEF and biomarkers of inflammation and extracellular matrix reorganization and have shown that AF parallels the metabolic and inflammatory comorbidities in HFpEF …”
Section: Epidemiological and Clinical Evidence Supporting Atrial Fibrmentioning
confidence: 99%
“…Biomarkers of systemic inflammation and collagen turnover are elevated in both AF and HFpEF and are associated with exercise intolerance and abnormalities in diastolic filling . Proteomic analyses suggest a strong link between HFpEF and biomarkers of inflammation and extracellular matrix reorganization and have shown that AF parallels the metabolic and inflammatory comorbidities in HFpEF …”
Section: Epidemiological and Clinical Evidence Supporting Atrial Fibrmentioning
confidence: 99%
“…Previous analyses in BIOSTAT‐CHF have shown that worse cardiovascular outcomes were seen in heart failure patients with AF compared to sinus rhythm . Nevertheless, after multivariable adjustment, the AF genetic risk score was not associated with all‐cause mortality.…”
Section: Discussionmentioning
confidence: 79%
“…Previous analyses in BIOSTAT-CHF have shown that worse cardiovascular outcomes were seen in heart failure patients with AF compared to sinus rhythm. 24 Nevertheless, after multivariable adjustment, the AF genetic risk score was not associated with all-cause mortality. However, a genetic risk score alone does not capture the clinical significance of AF presence in patients with an extensive cardiac substrate and other underlying risk factors.…”
Section: Atrial Fibrillation Genetic Risk Score and All-cause Mortalitymentioning
confidence: 99%
“…Overall, 100 patients with HF in this study were selected from the EU FP7 funded BIOSTAT‐CHF (A systems BIOlogy Study to TAilored Treatment in Chronic Heart Failure) project. This was a multicentre clinical study in Europe that aimed to identify poor outcomes in HF patients with standard treatment using a systems biology approach (including demographics, biomarkers, genetics, and proteomics) . This project was conducted according to the Declaration of Helsinki that was approved by national and local ethics committees.…”
Section: Methodsmentioning
confidence: 99%
“…This was a multicentre clinical study in Europe 14 that aimed to identify poor outcomes in HF patients with standard treatment using a systems biology approach (including demographics, biomarkers, genetics, and proteomics). [15][16][17][18][19][20][21][22][23][24][25][26][27] This project was conducted according to the Declaration of Helsinki that was approved by national and local ethics committees. All patients in this study had written informed consent.…”
Section: Patient Populationmentioning
confidence: 99%